Urban mountain waterscapes: the transformation of hydro-social relations in the Trans-Himalayan Town Leh, Ladakh, India - Müller-Blondeau, Judith Christine; Dame, Juliane; Nüsser, Marcus (Water, 2020)
Socio-economic processes and climate change impact the socio-hydrology of many small towns in the Hindu Kush Himalaya (HKH), such as Leh in Ladakh. The rapidly urbanising town experienced a shift from agricultural livelihoods towards incomes mainly relying on the tourism sector. As results of this research show, the limited water resources essential to the everyday life of urban citizens have become increasingly important for the tourism sector and the urbanisation process. This study aims to understand the transformation of the urban mountain waterscape and the role of different actors involved. The waterscape approach frames hydro-social relations in a specific spatial context and additionally captures diverging hydromentalities within local actor constellations. Related discourses are materialised as water governance impacting the everyday life of urban citizens. A combination of quantitative, qualitative and participatory methods allows for a differentiated picture of current developments. Based on 312 household questionnaires, 96 semi-structured interviews, and a participatory photography workshop, this study provides evidence that urban restructuring induced by development imaginaries produces uneven water citizenships in Leh. Along with socio-economic shifts, the community-managed water regulation system is replaced by a technocratic scheme, centralising water supply and sanitation. While some of Leh’s citizens benefit from urban restructurings, others are confronted with environmental and social costs, such as a deteriorating water quality and a further reduction in quantity.
Gesehen am 24.08.2020